A geochemical study of speleothems and cave waters in basaltic caves at Lava Beds National Monument, Northern California, USA - Ford, Joshua A. (Kansas State University, 2020)
Lava caves within Lava Beds National Monument (LBNM), CA, were selected as terrestrial analog sites for caves observed on other planetary bodies. The lava caves at LBNM were found to contain active microbial communities, including colorful biofilms. Additionally, the caves were discovered to host a variety of morphologically distinct secondary mineral deposits known as speleothems. Speleothems and co-located cave waters were collected to determine their compositions and assess geochemical biosignatures. Speleothems were analyzed for mineralogical, elemental, and internal stratigraphic contents. Cave waters were analyzed for major elements, major ions, DOC, and stable isotopes. Speleothems were found to be comprised primarily of opal-A and calcite, with elemental chemistries dominated by SiO₂ and CaO, alongside lesser concentrations of MgO. Speleothem formation was ultimately interpreted to be driven by both inorganic and biological factors, including availability of water, extent of evaporation, and nucleation influenced by microbial bioaccumulation. Mineral precipitation likely occurs due to evaporation of water films supplied by condensation and capillary action, with opal favored in wet conditions and calcite in dry conditions, where increased evaporative concentration favors the precipitation of calcite and Mg carbonate. Microbes likely mediate precipitation through nucleation of porous opal by bound silanol in microbial extracellular products. This creates a microsystem wherein autotrophic bacteria may encourage carbonate mineral precipitation via CO₂ consumption increasing pH, and may be reflected in the presence of both microstromatolite-like opal and calcite lamina and a predominance of DOC in cave waters. These findings contribute to the further understanding and characterization of lava cave speleothems as potential biosignature targets.
Keywords: Lava Cave; Speleothem; Cave waters; Biosignature; Terrestrial Analog